2014
DOI: 10.3928/1081597x-20141021-10
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Higher-Order Aberrations and Corneal Asphericity Between Wavefront-guided and Aspheric LASIK for Myopia

Abstract: Aspheric LASIK induced significantly less change in higher-order aberrations and maintained corneal asphericity better than wavefront-guided LASIK. The visual outcome and contrast sensitivity was better in the aspheric group at 6 months postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The visual outcome and contrast sensitivity were better in the aspheric group at 6 months postoperatively. In a study of forty patients were randomly selected to receive wavefrontguided LASIK (wavefront-guided group) and aspheric LASIK (aspheric group) (40 eyes of 20 patients in each group) using the Technolas 217z excimer laser platform (Bausch & Lomb, Rochester, NY) (6) . Toda et al in a prospective, randomized clinical study, 68 eyes of 35 patients undergoing LASIK were enrolled.…”
Section: Discussionmentioning
confidence: 99%
“…The visual outcome and contrast sensitivity were better in the aspheric group at 6 months postoperatively. In a study of forty patients were randomly selected to receive wavefrontguided LASIK (wavefront-guided group) and aspheric LASIK (aspheric group) (40 eyes of 20 patients in each group) using the Technolas 217z excimer laser platform (Bausch & Lomb, Rochester, NY) (6) . Toda et al in a prospective, randomized clinical study, 68 eyes of 35 patients undergoing LASIK were enrolled.…”
Section: Discussionmentioning
confidence: 99%
“…Gatinel et al 14 In later studies, many groups reported findings favoring an aspherically optimized ablation profile over the conventional profiles in terms of most postoperative refractive outcomes. [17][18][19] In a large-scale study including 400 eyes (200 eyes in the wavefront-optimized group and 200 eyes in the custom-Q group), Tawfik et al 20 reported a statistically significant difference in postoperative change in Q-values (P = .02) and postoperative visual acuity (P = .42) between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…16 Clinically, it has been shown that corneal vertex-centered treatments perform better in terms of induced ocular aberrations and asphericity in myopic eyes with moderate to large pupillary offset. 18 Many groups have explored the optimum corneal asphericity that must be targeted in refractive procedures. Patel et al 24 presented a model predicting that optimal optical imagery is produced when the corneal profile is represented by a flattening ellipse (shape factor = 0.65 to 0.85).…”
Section: Discussionmentioning
confidence: 99%
“…Q-value-guided femtosecond laser-assisted in situ keratomileusis (Q-FS-LASIK) is a safe surgical procedure in which lower spherical aberration is introduced [1][2][3][4], and it has been a popular procedure for corneal refractive surgery. Small-incision lenticular extraction (SMILE) is a new kind of surgical procedure that avoids flap-related complications [5][6] and is gaining more attention.…”
Section: Introductionmentioning
confidence: 99%